1996
DOI: 10.1016/0009-2509(96)00177-7
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst development for the selective methylation of catechol

Abstract: -Gas-phase alkylation of catechol with methanol on T-alumina and modified "t-alumina catalysts is studied experimentally. By limiting the conversion to X < 0.3, the formation of polymethylated species can be avoided and only the three isomers guaiacol, 3-methylcatechol and 4-methylcatechol are observed. Optimising the catalyst composition and the reaction conditions, a selectivity of 0.75 for the industrially most valuable product 3-methylcatechol can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…3 Available literature on the vapour phase alkylation of catechol over solid base catalysts, though limited, suggests that the basic sites are primarily responsible for the formation of C-/O-alkylated products. 4,5 This is further supported by the report that CO 2 adsorption over the basic sites leads to catalyst deactivation. 6,7 However, there is no evidence to suggest that the weak sites over the base catalysts are primarily important for the formation of mono oxy-methylated products, in particular guaiacol.…”
mentioning
confidence: 56%
“…3 Available literature on the vapour phase alkylation of catechol over solid base catalysts, though limited, suggests that the basic sites are primarily responsible for the formation of C-/O-alkylated products. 4,5 This is further supported by the report that CO 2 adsorption over the basic sites leads to catalyst deactivation. 6,7 However, there is no evidence to suggest that the weak sites over the base catalysts are primarily important for the formation of mono oxy-methylated products, in particular guaiacol.…”
mentioning
confidence: 56%
“…In our earlier study on the methylation of catechol over solid base catalysts, we had proposed that the presence of weak basic sites over the base catalysts were important for the formation of oxygen-alkylated products [6]. A few papers on alkylation of catechol over base catalysts have also suggested that the basic sites are responsible for the formation of O-/ C-alkylated products [4,22]. It is also suggested that the weak acidic sites may be responsible for the high activity and high selectivity for guaiacol in the methylation of catechol over phosphated catalysts [11].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several solid acid catalysts have been tried out for various alkylation reactions. Some of the solid acid catalysts studied for the title reaction were metal oxides [4][5][6][7][8][9], phosphates [10,11], ammonium metatungstate [12] and zeolites [13]. However, information on the alkylation of catechol over sulphatemodified zirconia (SZ) is rather limited [14,15] The surface areas of zirconia and sulphated zirconia samples were measured by Quantasorb AS-1 using N 2 as a probe molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in vapour-phase alkylation of catechol has increased for the reason that this route is more economical and more environmentally friendly for industrial applications. Several heterogeneous catalysts have been tested in the vapour-phase alkylation of catechol with methanol/ethanol, including various metal oxides, phosphates and zeolites [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%